Mixed coke, graphitized cathode carbon block and preparation method thereof

By calcining isotropic coke, asphalt coke and high-density high-sulfur coke, a low-sulfur content hybrid coke was prepared, which solved the problem of insufficient mechanical strength and wear resistance of graphitized cathode carbon blocks and improved its performance.

CN119265645APending Publication Date: 2025-01-07ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411525240.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the low sulfur content and high tap density of mixed coke, resulting in insufficient mechanical strength and wear resistance of graphitized cathode carbon blocks.

Method used

By mixing isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles, sulfur fraction is removed to obtain mixed cokes with low sulfur content, and used to prepare graphitized cathode carbon blocks.

Benefits of technology

The low sulfur content and high tap density of mixed coke are achieved, and the mechanical strength and wear resistance of graphitized cathode carbon blocks are improved, and the "bloating" phenomenon in the graphitization process is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265645A_ABST
    Figure CN119265645A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon materials for aluminum, in particular to mixed coke, a graphitized cathode carbon block and a preparation method of the graphitized cathode carbon block. The preparation method comprises the following steps: mixing isotropic coke particles, pitch coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles; carrying out first calcination on the mixed green coke particles to obtain calcined mixed coke raw material particles; performing secondary calcination on the low-sulfur coke particles to obtain calcined low-sulfur coke particles; mixing the calcined low-sulfur coke particles with the calcined mixed coke raw material particles to obtain mixed coke; wherein the temperature of the first calcination is greater than or equal to 1500 DEG C, and the time of the first calcination is greater than or equal to 20 hours; the second calcination temperature is greater than or equal to 1250 DEG C, and the second calcination time is greater than or equal to 60 minutes. According to the preparation method, the isotropic coke particles, the pitch coke particles and the high-density high-sulfur coke particles are mixed, and then the mixed coke with low sulfur content and high tap density can be obtained in a mode of combining high first calcination with second calcination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of carbon materials for aluminum, and in particular to a mixed coke, graphitized cathode carbon block and a preparation method thereof. Background Art

[0002] Petroleum coke is a by-product of oil refining. It is a solid product produced by a delayed coking unit using residual oil as raw material. Generally, the production of graphitized cathode carbon blocks for aluminum requires low-sulfur petroleum coke with a sulfur content of less than 0.7%. This type of coke only accounts for 7% of my country's petroleum coke production. This part of low-sulfur coke has been used to produce graphite electrodes and recarburizers. However, in the context of energy reduction and comprehensive utilization of resources, graphite cathode carbon blocks will be completely replaced by graphitized cathode carbon blocks; at this stage, negative electrode materials for new energy batteries have also joined the battle for low-sulfur coke, causing a shortage of petroleum coke resources. Since low-sulfur petroleum coke has the characteristics of soft texture and low tap density, these characteristics will cause the mechanical strength of graphitized cathode carbon blocks to be low and the wear resistance to be poor.

[0003] Isotropic coke, pitch coke and high-density high-sulfur coke have the advantages of high tap density and high hardness, and can be used to partially replace low-sulfur petroleum coke to produce graphitized cathode carbon blocks, thereby improving the mechanical strength and wear resistance of graphitized cathode carbon blocks. However, since the sulfur content in the mixed coke obtained by directly mixing isotropic coke and high-density high-sulfur coke is generally too high, the mixed coke with too high sulfur content will cause cracks in the cathode roasted block during the subsequent graphitization process of the cathode roasted block, and the advantage of high tap density of isotropic coke and high-density high-sulfur coke cannot be brought into play, so the volume density and mechanical strength of the cathode roasted block cannot be affected by the mixed coke. Summary of the invention

[0004] The present application provides a mixed coke, a graphitized cathode carbon block and a preparation method thereof to solve the following technical problem: how to balance low sulfur content and high tap density in the mixed coke.

[0005] In a first aspect, the present application provides a method for preparing mixed coke, the preparation method comprising:

[0006] Mixing isotropic coke particles, pitch coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles;

[0007] The mixed raw coke particles are subjected to a first calcination to obtain calcined mixed coke raw material particles;

[0008] The low-sulfur coke particles are subjected to a second calcination to obtain calcined low-sulfur coke particles;

[0009] Mixing the calcined low-sulfur coke particles and the calcined mixed coke raw material particles to obtain mixed coke;

[0010] Wherein, the temperature of the first calcination is ≥1500°C, and the time of the first calcination is ≥20h;

[0011] The temperature of the second calcination is ≥1250° C., and the time of the second calcination is ≥60 min.

[0012] Optionally, the temperature of the first calcination is 1500° C. to 2200° C., and the time of the first calcination is 20 h to 50 h;

[0013] The temperature of the second calcination is 1250° C. to 1350° C., and the time of the second calcination is 60 min to 2100 min.

[0014] Optionally, the weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=(20-100):(0-50):(0-50).

[0015] Optionally, the weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=(5-40):(60-95).

[0016] Optionally, the isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is less than 7% of the total weight of the isotropic coke particles, and the weight content of the first ash component is less than 0.6% of the total weight of the isotropic coke particles; and / or,

[0017] The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is less than 0.1% of the total weight of the asphalt coke particles, and the weight content of the second ash component is less than 0.8% of the total weight of the asphalt coke particles; and / or,

[0018] The high-density high-sulfur coke particles include a third sulfur component and a third ash component, wherein the weight content of the third sulfur component is less than 7% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash component is less than 0.6% of the total weight of the high-density high-sulfur coke particles.

[0019] Optionally, the calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component, wherein the weight content of the fourth sulfur component is less than 0.7% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is less than 1.0% of the total weight of the calcined mixed coke raw material particles.

[0020] Optionally, the calcined mixed coke raw material particles include at least one of the following properties:

[0021] The true density of the calcined mixed coke raw material particles is greater than or equal to 2.10 g / cm3 ;

[0022] The powder resistivity of the calcined mixed coke raw material particles is less than or equal to 400 μΩ·m;

[0023] The tap density of the fine-grained material in the calcined mixed coke raw material particles is greater than or equal to 0.90 g / cm 3 The particle size of the fine-grained material is 1 mm to 2 mm.

[0024] In a second aspect, the present application provides a mixed coke, which is obtained by the preparation method described in the first aspect.

[0025] In a third aspect, the present application provides a graphitized cathode carbon block, wherein the cathode carbon block comprises the mixed coke described in the second aspect.

[0026] In a fourth aspect, the present application provides a method for preparing the graphitized cathode carbon block according to the third aspect, the method comprising:

[0027] heating the mixed coke to obtain preheated dry material;

[0028] Adding the preheated dry material into liquid coal tar and heating and kneading the mixture to obtain a mixed paste;

[0029] Molding the mixed paste to obtain a molded green block;

[0030] The formed green block is calcined, graphitized and processed to obtain a graphitized cathode carbon block.

[0031] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0032] A method for preparing mixed coke is provided in an embodiment of the present application. The method first mixes isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles. The isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles all have the characteristics of high tap density and high hardness, so as to improve the tap density and hardness of the mixed green coke particles and facilitate the subsequent first calcination. In addition, the temperature of the first calcination is ≥1500°C, and the time of the first calcination is ≥20h. The high sulfur content of the mixed green coke particles is mostly removed by calcination at a higher first calcination temperature. In addition, the temperature of the second calcination is ≥1250°C, and the time of the second calcination is ≥60min. The sulfur content of the low-sulfur coke particles is partially removed by the second calcination. Then, the calcined low-sulfur coke and the calcined mixed coke raw material particles with low sulfur content are mixed to obtain a low-sulfur mixed coke. Therefore, the preparation method can take into account both the low sulfur content and the high tap density of the mixed coke. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0035] Figure 1 A schematic diagram of a process for preparing mixed coke provided in an embodiment of the present application;

[0036] Figure 2 A schematic flow chart of a method for preparing a graphitized cathode carbon block provided in an embodiment of the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0038] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0039] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] Figure 1 A schematic flow chart of a method for preparing mixed coke provided in an embodiment of the present application is exemplarily shown;

[0041] like Figure 1 As shown, the present application embodiment provides a method for preparing mixed coke, the preparation method comprising:

[0042] S1. mixing isotropic coke particles, pitch coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles;

[0043] S2. The mixed raw coke particles are first calcined to obtain calcined mixed coke raw material particles;

[0044] S3. The low-sulfur coke particles are subjected to a second calcination to obtain calcined low-sulfur coke particles;

[0045] S4. The calcined low-sulfur coke particles and the calcined mixed coke raw material particles are mixed to obtain mixed coke;

[0046] Wherein, the temperature of the first calcination is ≥1500°C, and the time of the first calcination is ≥20h;

[0047] The temperature of the second calcination is ≥1250° C., and the time of the second calcination is ≥60 min.

[0048] It should be noted that the equipment used for the second calcination of the low-sulfur coke particles can be a pot calcining furnace or a rotary kiln.

[0049] It should be noted that when a pot calciner is used to carry out the second calcination of low-sulfur coke particles, the second calcination time can be 20 hours to 34 hours; when a rotary kiln is used to carry out the second calcination of low-sulfur coke particles, the second calcination time can be 60 minutes to 80 minutes.

[0050] It should be noted that the equipment used for the first calcination of the mixed green coke particles may be an electric calcination furnace.

[0051] It should be noted that the calcined mixed coke raw material particles and the calcined low-sulfur coke particles can be prepared into coarse particles, medium particles, fine particles or powder particles, etc. according to the requirements of the production of dry material particle size.

[0052] It should be noted that the isotropic coke particles are cokes with a fine-grained structure that exhibit similar properties in all directions. On the other hand, anisotropic coke has a coarse structure with a layered structure, and its properties vary with orientation. Shot coke is a form of isotropic coke and delayed petroleum coke with a unique structure, appearing as relatively hard, dense, non-porous single or molten spherical 2mm to 6mm bead clusters.

[0053] It should be noted that the asphalt coke particles are products obtained by direct coking of coal tar (medium-temperature asphalt or hard asphalt) in a coking furnace. They can also be produced by a delayed coking method, in which the final coking temperature is above 1100°C.

[0054] It should be noted that the high-density high-sulfur coke particles refer to particles with a sulfur content of more than 3% and a tap density (2mm-1mm) higher than 0.85g / cm 3 The high-density and high-sulfur petroleum coke can be used as a raw material for producing silicon carbide (abrasive material), calcium carbide (calcium carbide), metallic silicon, prebaked anodes and other carbon products.

[0055] In some optional embodiments,

[0056] The temperature of the first calcination is 1500°C to 2200°C, and the time of the first calcination is 20h to 50h;

[0057] The temperature of the second calcination is 1250°C to 1350°C, and the time of the second calcination is 60min to 2100min;

[0058] In these embodiments, the temperature of the first calcination can be 1500°C to 2200°C, and the time of the first calcination can be 20h to 50h. The mixed green coke is desulfurized by the higher first calcination temperature to obtain a low-sulfur mixed coke. In addition, the temperature of the second calcination can be 1250°C to 1350°C, and the time of the second calcination can be 60min to 2100min. The sulfur in the low-sulfur coke particles is removed by the second calcination to obtain a calcined low-sulfur coke with a lower sulfur content.

[0059] The temperature of the first calcination may be 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C or 2200°C.

[0060] The time of the first calcination can be 20 h, 25 h, 30 h, 35 h, 40 h, 45 h or 50 h.

[0061] The temperature of the second calcination may be 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C or 1350°C.

[0062] The calcination temperature may be 1250°C to 1350°C in a pot furnace or a rotary kiln, or 1500°C to 2200°C in an electric calcination furnace.

[0063] The calcination time can be 60 minutes to 80 minutes in a rotary kiln, 20 hours to 34 hours in a pot furnace, or 20 hours to 50 hours in an electric calcining furnace.

[0064] In some optional embodiments, the weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles, and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=(20-100):(0-50):(0-50);

[0065] In these embodiments, the weight m1 of the isotropic coke particles, the weight m2 of the asphalt coke particles and the weight m3 of the high-density high-sulfur coke particles can satisfy the relationship: m1:m2:m3=(20-100):(0-50):(0-50). Since the isotropic coke particles, the asphalt coke particles and the high-density high-sulfur coke particles all have the characteristics of higher tap density and higher hardness, the tap density and hardness of the mixed green coke particles can be improved, and the subsequent calcination can be facilitated. The sulfur content in the mixed green coke raw material particles can be reduced by higher calcination temperature and longer calcination time, so that a mixed coke with a low sulfur content can be obtained.

[0066] The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles can satisfy the relationship: m1:m2:m3=20:0:0, 20:0:25, 20:0:50, 20:25:0, 20:25:25, 20:25:50, 20:50:0, 20:50:25, 20:50:50, 40:0:0, 40:0:25, 40:0:50, 40:25:0, 40:25:25, 40:25:50, 40:50:0, 40:50:25, 40:50:50, 60:0:0, 60:0:25 , 60:0:50, 60:25:0, 60:25:25, 60:25:50, 60:50:0, 60:50:25, 60:50:50, 80:0:0, 80:0:25, 80:0:50, 80:25:0, 80:25:25, 80:25:50, 80:50:0, 80:50:25, 80:50:50, 100:0:0, 100:0:25, 100:0:50, 100:25:0, 100:25:25, 100:25:50, 100:50:0, 100:50:25, or 100:50:50.

[0067] In some optional embodiments, the weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=(5-40):(60-95);

[0068] In these embodiments, the weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles can satisfy the relationship: m4:m5=(5-40):(60-95). By using calcined mixed coke raw material particles with a low sulfur content to replace the calcined low-sulfur coke particles, a mixed coke with a low sulfur content can be obtained. In addition, the tap density and hardness of the mixed coke can be improved by using the isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles with higher tap density and higher hardness contained in the calcined mixed coke raw material particles.

[0069] The weight m4 of the calcined mixed coke raw material powder and the weight m5 of the calcined low-sulfur coke powder can satisfy the relationship: m4:m5=5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65 or 40:60.

[0070] In some optional embodiments, the isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is less than 7% of the total weight of the isotropic coke particles, and the weight content of the first ash component is less than 0.6% of the total weight of the isotropic coke particles; and / or,

[0071] The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is less than 0.5% of the total weight of the asphalt coke particles, and the weight content of the second ash component is less than 0.8% of the total weight of the asphalt coke particles; and / or,

[0072] The high-density high-sulfur coke particles include a third sulfur component and a third ash component, wherein the weight content of the third sulfur component is less than 7% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash component is less than 0.6% of the total weight of the high-density high-sulfur coke particles;

[0073] In these embodiments, the isotropic coke particles may include a first sulfur content and a first ash content, and the weight content of the first sulfur content may be less than 7% of the total weight of the isotropic coke powder, and the weight content of the first ash content may be less than 0.6% of the total weight of the isotropic coke powder, indicating that the isotropic coke particles have a higher sulfur content and a lower ash content, which facilitates the subsequent desulfurization of the mixed green coke particles by calcination to reduce the sulfur content in the mixed green coke raw material particles, thereby obtaining a low-sulfur mixed coke; in addition, the asphalt coke particles may include a second sulfur content and a second ash content, and the weight content of the second sulfur content may be less than 0.5% of the total weight of the asphalt coke particles, and the weight content of the second ash content may be less than 0.8% of the total weight of the asphalt coke. This indicates that the asphalt coke particles have lower sulfur content and lower ash content, which facilitates the subsequent desulfurization of the mixed green coke particles through the first calcination method to reduce the sulfur content in the mixed green coke raw material particles, thereby obtaining mixed coke particles with a low sulfur content; in addition, the high-density high-sulfur coke particles may include a third sulfur content and a third ash content, and the weight content of the third sulfur content may be less than 7% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash content may be less than 0.6% of the total weight of the high-density high-sulfur coke particles, indicating that the high-density high-sulfur coke particles have higher sulfur elements and less ash impurities, which facilitates the subsequent desulfurization of the mixed green coke particles through the first calcination method to reduce the sulfur content in the mixed green coke particles, thereby obtaining mixed coke with a low sulfur content.

[0074] In some optional embodiments, the calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component, wherein the weight content of the fourth sulfur component is less than 0.7% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is less than 1.0% of the total weight of the calcined mixed coke raw material particles;

[0075] In these embodiments, the calcined mixed coke raw material particles may include a fourth sulfur component and a fourth ash component, and the weight content of the fourth sulfur component is less than 0.7% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component may be less than 1.0% of the total weight of the calcined mixed coke raw material particles, which indicates that the sulfur content and ash content in the mixed coke particles can be effectively reduced by the first calcination method.

[0076] In some optional embodiments, the calcined mixed coke raw material particles include at least one of the following properties:

[0077] The true density of the calcined mixed coke raw material particles is greater than or equal to 2.10 g / cm 3 ;

[0078] The powder resistivity of the calcined mixed coke raw material particles is less than or equal to 400 μΩ·m;

[0079] The tap density of the fine-grained material in the calcined mixed coke raw material particles is greater than or equal to 0.90 g / cm 3 , the particle size of the fine-grained material is 1 mm to 2 mm;

[0080] In these embodiments, the true density of the calcined mixed coke raw material particles may be greater than or equal to 2.10 g / cm 3 , and the powder resistivity of the calcined mixed coke raw material particles can be less than or equal to 400μΩ·m, and the tap density of the fine-grained material in the calcined mixed coke raw material particles can be greater than or equal to 0.90g / cm 3 This indicates that the calcined mixed coke raw material particles have a higher tap density. The tap density and hardness of the mixed coke can be improved by replacing part of the calcined low-sulfur coke particles with calcined mixed coke raw material particles.

[0081] Based on a general inventive concept, an embodiment of the present application provides a mixed coke, which is obtained by the preparation method.

[0082] The mixed coke is realized based on the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the mixed coke adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.

[0083] Based on a general inventive concept, an embodiment of the present application provides a graphitized cathode carbon block, wherein the cathode carbon block includes the mixed coke.

[0084] The graphitized cathode carbon block is realized based on the above-mentioned mixed coke. The specific composition of the mixed coke can refer to the above-mentioned embodiment. Since the graphitized cathode carbon block adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0085] Figure 2 A schematic flow chart of a method for preparing a graphitized cathode carbon block provided in an embodiment of the present application is shown exemplarily;

[0086] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a method for preparing the graphitized cathode carbon block, the method comprising:

[0087] S1. Mixing and heating the mixed coke to obtain a preheated dry material;

[0088] S2. The preheated dry material is added to the liquid coal tar and heated and kneaded to obtain a mixed paste;

[0089] S3. The mixed paste is molded to obtain a green block;

[0090] S4. The formed green blocks are calcined, graphitized and processed to obtain graphitized cathode carbon blocks.

[0091] This method is a method for preparing the above-mentioned graphitized cathode carbon block. The specific composition of the graphitized cathode carbon block can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.

[0092] It should be noted that the molding method can be vibration molding or extrusion molding.

[0093] It should be noted that the calcination temperature may be 1000°C to 1250°C; the graphitization temperature may be 2500°C to 3000°C.

[0094] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0095] Example 1

[0096] like Figure 1 As shown, a method for preparing mixed coke comprises:

[0097] S1. mixing isotropic coke particles, pitch coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles;

[0098] S2. The mixed raw coke particles are first calcined to obtain calcined mixed coke raw material particles;

[0099] S3. The low-sulfur coke particles are subjected to a second calcination to obtain calcined low-sulfur coke particles;

[0100] S3. The calcined low-sulfur coke particles and the calcined mixed coke raw material particles are mixed to obtain a mixed coke;

[0101] The temperature of the first calcination is 2000°C and the time of the first calcination is 36h.

[0102] The second calcination temperature was 1340° C. and the calcination time was 1200 min.

[0103] The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=25:50:25.

[0104] The weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=10:90.

[0105] The isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is 4.9% of the total weight of the isotropic coke particles, and the weight content of the first ash component is 0.4% of the total weight of the isotropic coke particles;

[0106] The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is 0.4% of the total weight of the asphalt coke particles, and the weight of the second ash component is 0.7% of the total weight of the asphalt coke particles;

[0107] The high-density high-sulfur coke particles include a third sulfur component and a third ash component. The weight of the third sulfur component is 6.5% of the total weight of the high-density high-sulfur coke particles, and the weight of the third ash component is 0.5% of the total weight of the high-density high-sulfur coke particles.

[0108] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.2% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.4% of the total weight of the calcined mixed coke raw material particles.

[0109] The properties of calcined mixed coke raw material particles include:

[0110] The true density of the calcined mixed coke raw material particles is 2.15g / cm 3 ;

[0111] The powder resistivity of the calcined mixed coke raw material particles is 0.332Ω·m;

[0112] The tap density of fine particles in the calcined mixed coke raw material particles is 0.91g / cm 3 , the particle size of fine-grained materials is 1mm~2mm.

[0113] The obtained mixed coke is used to prepare a graphitized cathode carbon block, and the specific steps include:

[0114] S1. Mixing the mixed coke to obtain a carbon block raw material;

[0115] S2. Preheating the dry material and heating and kneading the liquid coal tar to obtain a mixed paste;

[0116] S3. The mixed paste is molded to obtain a molded green block;

[0117] S4. The formed green block is calcined at 1250° C., graphitized at 2500° C., and processed to obtain a graphitized cathode carbon block.

[0118] The volume density of the graphitized cathode carbon block obtained is 1.66 g / cm 3 .

[0119] Example 2

[0120] Based on the contents disclosed in Example 1, the following modifications are further made:

[0121] The temperature of the first calcination is 1550°C, and the time of the first calcination is 20h;

[0122] The temperature of the second calcination is 1260° C., and the time of the second calcination is 60 min.

[0123] The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=90:5:5.

[0124] The weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=20:80.

[0125] The isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is 1.9% of the total weight of the isotropic coke particles, and the weight content of the first ash component is 0.3% of the total weight of the isotropic coke particles;

[0126] The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is 0.1% of the total weight of the asphalt coke particles, and the weight content of the second ash component is 0.6% of the total weight of the asphalt coke particles;

[0127] The high-density high-sulfur coke particles include a third sulfur component and a third ash component. The weight content of the third sulfur component is 3.1% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash component is 0.1% of the total weight of the high-density high-sulfur coke particles.

[0128] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.6% of the total weight of the calcined mixed coke raw material particles, and the weight of the fourth ash component is 0.4% of the total weight of the calcined mixed coke raw material particles.

[0129] The properties of calcined mixed coke raw material particles include:

[0130] The true density of the calcined mixed coke raw material particles is 2.17g / cm 3 ;

[0131] The powder resistivity of the calcined mixed coke raw material particles is 0.367Ω·m;

[0132] The tap density of fine particles in the calcined mixed coke raw material particles is 1.05g / cm 3 , the particle size of fine-grained materials is 1mm~2mm.

[0133] The volume density of the graphitized cathode carbon block obtained is 1.72 g / cm 3 .

[0134] Example 3

[0135] Based on the contents disclosed in Example 1, the following modifications are further made:

[0136] The first calcination temperature is 2050°C and the first calcination time is 40h.

[0137] The second calcination temperature was 1330°C and the calcination time was 34 h.

[0138] The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=50:5:45.

[0139] The weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=15:85.

[0140] The isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is 6.8% of the total weight of the isotropic coke particles, and the weight content of the first ash component is 0.5% of the total weight of the isotropic coke particles;

[0141] The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is 0.2% of the total weight of the asphalt coke particles, and the weight content of the second ash component is 0.4% of the total weight of the asphalt coke particles;

[0142] The high-density high-sulfur coke particles include a third sulfur component and a third ash component. The weight content of the third sulfur component is 3.7% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash component is 0.2% of the total weight of the high-density high-sulfur coke particles.

[0143] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.2% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.3% of the total weight of the calcined mixed coke raw material particles.

[0144] The properties of calcined mixed coke raw material particles include:

[0145] The true density of the calcined mixed coke raw material particles is 2.16g / cm 3 ;

[0146] The powder resistivity of the calcined mixed coke raw material particles is 0.390Ω·m;

[0147] The tap density of fine particles in the calcined mixed coke raw material particles is 0.98g / cm 3 , the particle size of fine-grained materials is 1mm~2mm.

[0148] The volume density of the graphitized cathode carbon block obtained is 1.68 g / cm 3 .

[0149] Comparative Example 1

[0150] Based on the contents disclosed in Example 1, the following modifications are further made:

[0151] The temperature of the first calcination is 1400°C, and the time of the first calcination is 10h;

[0152] The temperature of the second calcination is 1200° C., and the time of the second calcination is 40 min.

[0153] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.7% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.9% of the total weight of the calcined mixed coke raw material particles.

[0154] The tap density of fine particles in the calcined mixed coke raw material particles is 0.82g / cm 3 .

[0155] The volume density of the graphitized cathode carbon block obtained is 1.62 g / cm3 .

[0156] Comparative Example 2

[0157] Based on the contents disclosed in Example 1, the following modifications are further made:

[0158] The temperature of the first calcination is 2500°C, and the time of the first calcination is 60h;

[0159] The temperature of the second calcination is 1400° C., and the time of the second calcination is 2400 min.

[0160] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.05% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.2% of the total weight of the calcined mixed coke raw material particles.

[0161] The tap density of fine particles in the calcined mixed coke raw material particles is 0.72g / cm 3 .

[0162] The volume density of the graphitized cathode carbon block obtained is 1.55 g / cm 3 .

[0163] Comparative Example 3

[0164] Based on the contents disclosed in Example 1, the following modifications are further made:

[0165] Without adding isotropic coke particles, the weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=0:50:50.

[0166] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.2% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.4% of the total weight of the calcined mixed coke raw material particles.

[0167] The tap density of fine particles in the calcined mixed coke raw material particles is 0.83g / cm 3 .

[0168] The volume density of the graphitized cathode carbon block obtained is 1.63 g / cm 3 .

[0169] Comparative Example 4

[0170] Based on the contents disclosed in Example 1, the following modifications are further made:

[0171] The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=10:50:40.

[0172] The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component. The weight content of the fourth sulfur component is 0.2% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is 0.4% of the total weight of the calcined mixed coke raw material particles.

[0173] The tap density of fine particles in the calcined mixed coke raw material particles is 0.78g / cm 3 .

[0174] The volume density of the graphitized cathode carbon block obtained is 1.59 g / cm 3 .

[0175] In summary, the embodiment of the present application provides a method for preparing a mixed coke. The method first mixes isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles with higher tap density and higher hardness, and then removes the high sulfur content of the mixed green coke particles through a higher first calcination temperature. In addition, the sulfur content of the low-sulfur coke particles is partially removed through a second calcination. Then, the calcined low-sulfur coke and the low-sulfur calcined mixed coke raw material particles are mixed to obtain a low-sulfur mixed coke, thereby achieving a balance between low sulfur content and higher tap density of the mixed coke.

[0176] In addition, a graphitized cathode carbon block is provided in an embodiment of the present application, which can solve the "gas swelling" phenomenon in the graphitization process through mixed coke with a low sulfur content; in addition, the graphitized cathode carbon block is based on the advantages of high tap density and high hardness of isotropic coke particles, asphalt coke particles and high-density high-sulfur coke particles in the mixed coke, which can improve the mechanical strength and wear resistance of the graphitized cathode carbon block.

[0177] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A method for preparing mixed coke, characterized in that: The preparation method comprises: Mixing isotropic coke particles, pitch coke particles and high-density high-sulfur coke particles to obtain mixed green coke particles; The mixed raw coke particles are subjected to a first calcination to obtain calcined mixed coke raw material particles; The low-sulfur coke particles are subjected to a second calcination to obtain calcined low-sulfur coke particles; Mixing the calcined low-sulfur coke particles and the calcined mixed coke raw material particles to obtain mixed coke; Wherein, the temperature of the first calcination is ≥1500°C, and the time of the first calcination is ≥20h; The temperature of the second calcination is ≥1250° C., and the time of the second calcination is ≥60 min.

2. The preparation method according to claim 1, characterized in that: The temperature of the first calcination is 1500° C. to 2200° C., and the time of the first calcination is 20 h to 50 h; The temperature of the second calcination is 1250° C. to 1350° C., and the time of the second calcination is 60 min to 2100 min.

3. The preparation method according to claim 1, characterized in that: The weight m1 of the isotropic coke particles, the weight m2 of the pitch coke particles and the weight m3 of the high-density high-sulfur coke particles satisfy the relationship: m1:m2:m3=(20-100):(0-50):(0-50).

4. The preparation method according to claim 1, characterized in that: The weight m4 of the calcined mixed coke raw material particles and the weight m5 of the calcined low-sulfur coke particles satisfy the relationship: m4:m5=(5-40):(60-95).

5. The preparation method according to claim 1, characterized in that: The isotropic coke particles include a first sulfur component and a first ash component, wherein the weight content of the first sulfur component is less than 7% of the total weight of the isotropic coke particles, and the weight content of the first ash component is less than 0.6% of the total weight of the isotropic coke particles; and / or, The asphalt coke particles include a second sulfur component and a second ash component, wherein the weight content of the second sulfur component is less than 0.5% of the total weight of the asphalt coke particles, and the weight content of the second ash component is less than 0.8% of the total weight of the asphalt coke particles; and / or, The high-density high-sulfur coke particles include a third sulfur component and a third ash component, wherein the weight content of the third sulfur component is less than 7% of the total weight of the high-density high-sulfur coke particles, and the weight content of the third ash component is less than 0.6% of the total weight of the high-density high-sulfur coke particles.

6. The preparation method according to claim 1, characterized in that: The calcined mixed coke raw material particles include a fourth sulfur component and a fourth ash component, wherein the weight content of the fourth sulfur component is less than 0.7% of the total weight of the calcined mixed coke raw material particles, and the weight content of the fourth ash component is less than 1.0% of the total weight of the calcined mixed coke raw material particles.

7. The preparation method according to claim 6, characterized in that: The calcined mixed coke raw material particles include at least one of the following properties: The true density of the calcined mixed coke raw material particles is greater than or equal to 2.10 g / cm 3 ; The powder resistivity of the calcined mixed coke raw material particles is less than or equal to 400 μΩ·m; The tap density of the fine-grained material in the calcined mixed coke raw material particles is greater than or equal to 0.90 g / cm 3 The particle size of the fine-grained material is 1 mm to 2 mm.

8. A mixed coke, characterized in that: The mixed coke is obtained by the preparation method according to any one of claims 1 to 7.

9. A graphitized cathode carbon block, characterized in that: The cathode carbon block comprises the mixed coke as claimed in claim 8.

10. A method for preparing the graphitized cathode carbon block according to claim 9, characterized in that: The method comprises: heating the mixed coke to obtain preheated dry material; Adding the preheated dry material into liquid coal tar, heating and kneading to obtain a mixed paste; Molding the mixed paste to obtain a molded green block; The formed green block is calcined, graphitized and processed to obtain a graphitized cathode carbon block.